Pembangunan Sistem Pengelolaan Indekos pada Vinokost berbasis Web dengan Memanfaatkan Payment Gateway - Hamim Nizar Yudistira; Diah Priharsari; Nanang Yudi Setiawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Vinokost is one of the boarding houses in Malang City. This boarding house is close to various well-known university in Malang City. The existing management or administrative system at Vinokost uses simple recording on books and receipts for payment. Payments made by boarding house residents are also still in cash. The occupants or renters of the boarding house must go to the automated teller machine to withdraw the money which will then be paid to the boarding house manager. This process certainly does not take a short time. Therefore, a web-based information system is needed to facilitate the management of boarding houses and is also integrated into the payment gateway to facilitate payments. The Vinokost boarding house management system was built by adapting the Waterfall development method. There are 5 stages, namely data mining, requirements analysis, system design, implementation, and testing. The boarding house management system is developed using the Laravel framework for the backend and Bootstrap for the frontend. The database used is MySQL with the help of phpMyAdmin. As for the payment gateway using services from Midtrans. In the tests carried out using Black Box Testing, the status of 100% successful means that the requirements that must be met by the system have been met.